Heavy and light minerals at DSDP Leg 67 Holes - Sachindra Prasad; Reinhard Hesse (PANGAEA, 1982)
Heavy and light minerals were examined in 29 samples from Sites 494, 498, 499, 500, and 495 on the Deep Sea Drilling Project Leg 67 Middle America Trench transect; these sites represent lower slope, trench, and oceanic crust environments off Guatemala. All samples are Quaternary except those from Hole 494A (Pliocene) and Hole 498A (Miocene). Heavy-mineral assemblages of the Quaternary sediments are characterized by an immature pyroxene-amphibole suite with small quantities of olivine and epidote. The Miocene sediments yielded an assemblage dominated by epidote and pyroxene but lacking olivine; the absence of olivine is attributed to selective removal of the most unstable components by intrastratal solution. Light-mineral assemblages of all samples are predominantly characterized by volcanic glass and plagioclase feldspar. The feldspar compositions are compatible with andesitic source rocks and frequently exhibit oscillatory zoning. The heavy- and light-mineral associations of these sediments suggest a proximal volcanic source, most probably the Neogene highland volcanic province of Guatemala. Sand-sized components from Site 495 are mainly biogenic skeletons and volcanic glass and, in one instance (Section 495-5-3), euhedral crystals of gypsum.
Supplement to: Prasad, S; Hesse, R (1982): Provenance of detrital sediments from the Middle America Trench transect off Guatemala, Deep Sea Drilling Project Leg 67. In: Abouin, J; von Huene, R; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 67, 507-514, https://doi.org/10.2973/dsdp.proc.67.118.1982